2018
DOI: 10.1093/hmg/ddy182
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod phosphate inhibits astrocyte inflammatory activity in mucolipidosis IV

Abstract: Mucolipidosis IV (MLIV) is an orphan neurodevelopmental disease that causes severe neurologic dysfunction and loss of vision. Currently there is no therapy for MLIV. It is caused by loss of function of the lysosomal channel mucolipin-1, also known as TRPML1. Knockout of the Mcoln1 gene in a mouse model mirrors clinical and neuropathological signs in humans. Using this model, we previously observed robust activation of microglia and astrocytes in early symptomatic stages of disease. Here we investigate the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 77 publications
7
33
0
Order By: Relevance
“…In non-obese diabetes EAE mice, FTY720 administration resulted in the decreased expression of reactive A1 astrocytic factors (including manganese-dependent superoxide dismutase (MnSOD), IL-6, CCL2, CXCL10, IL-1β, TNFα), and an upregulation of CXCL12 and IL-33 [65]. This effect of FTY720 on pro-inflammatory cytokines was confirmed in other rodent disease models [47,48,54,84,87,91]. Furthermore, the expression and secretion of pro-inflammatory cytokines in vitro was also reduced following treatment with FTY720 in both human and rodent primary cells from fetal and adult origin [65,73,[92][93][94] as well as in an astrocytoma cell line [95], while only one study has reported no effect of FTY720 on IL-1β and CCL2 [96].…”
Section: Astrocytesmentioning
confidence: 69%
“…In non-obese diabetes EAE mice, FTY720 administration resulted in the decreased expression of reactive A1 astrocytic factors (including manganese-dependent superoxide dismutase (MnSOD), IL-6, CCL2, CXCL10, IL-1β, TNFα), and an upregulation of CXCL12 and IL-33 [65]. This effect of FTY720 on pro-inflammatory cytokines was confirmed in other rodent disease models [47,48,54,84,87,91]. Furthermore, the expression and secretion of pro-inflammatory cytokines in vitro was also reduced following treatment with FTY720 in both human and rodent primary cells from fetal and adult origin [65,73,[92][93][94] as well as in an astrocytoma cell line [95], while only one study has reported no effect of FTY720 on IL-1β and CCL2 [96].…”
Section: Astrocytesmentioning
confidence: 69%
“…Even though we are able to exclude a role for the IFN pathway in primary pathology, components of this pathway are nevertheless the top elevated pathway in the nGD brain and are also elevated in a number of other LSDs, including mucolipidosis type IV and Krabbe disease [32,33], along with a number of other unrelated neuroinflammatory disorders [34]. This raises the question of how this pathway is activated.…”
Section: Discussionmentioning
confidence: 85%
“…Based on the existing natural history data in MLIV patients and our observations in the Mcoln1 −/− mouse, MLIV can be thought of as having two distinct phases: the developmental phase, associated with early-onset delayed oligodendrocyte maturation and gliosis (Grishchuk et al, 2014;Weinstock et al, 2018), and the late degenerative phase, associated with partial loss of Purkinje cells in the MLIV mouse (Micsenyi et al, 2009) and mild cerebellar atrophy in some MLIV patients (Frei et al, 1998). Understanding the timing and mechanisms behind these distinct events is important for designing and testing therapies.…”
Section: Introductionmentioning
confidence: 94%